2017
DOI: 10.14202/vetworld.2017.869-872
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic uses of epicatechin in diabetes and cancer

Abstract: Epicatechin is a natural flavonoid found in green tea. It has been reported to possess an immense antioxidant effect which contributes to its therapeutic effect against a handful of ailments. In this review, we discuss its therapeutic role in the management of two of the most important human diseases; diabetes and cancer. The consumption of epicatechin has been shown to reduce blood glucose levels in diabetic patients, while is anticancer effect was attributed to its antioxidant properties, antiangiogenic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 41 publications
2
40
0
Order By: Relevance
“…In this study, HPLC of PPE showed a significant amount of various phenolic compounds and flavonoids, thereby indicating that the extract could be useful in reducing inflammation. Catechin hydrate [30], (−) epicatechin [31] and p-coumaric acid [32] are natural phenolic compounds and flavonoids which act as potent antioxidants to scavenge free radicals in the body. Quercetin is also categorized as a flavonoid which exerts antioxidant activity, thereby useful in various anti-inflammatory diseases [33].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HPLC of PPE showed a significant amount of various phenolic compounds and flavonoids, thereby indicating that the extract could be useful in reducing inflammation. Catechin hydrate [30], (−) epicatechin [31] and p-coumaric acid [32] are natural phenolic compounds and flavonoids which act as potent antioxidants to scavenge free radicals in the body. Quercetin is also categorized as a flavonoid which exerts antioxidant activity, thereby useful in various anti-inflammatory diseases [33].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these polyphenols were extracted in this study in great abundance (≥1000 µg/g dw). First of them is epicatechin (>1300 µg/g dw), it was reported that the consumption of epicatechin reduces blood glucose levels in diabetic patients and has an anticancer effect, which was attributed to its antioxidant properties, as well as antiangiogenic and direct cytotoxicity to cancer cells [44]. The second one is procyanidin B2 (>1500 µg/g dw).…”
Section: -Hba 4-hca Ca 4-mbamentioning
confidence: 99%
“…This compound acts in beta-cell damage prevention, as shown in rats. Additionally, studies performed in diabetic animal models with either epicatechin or a crude alcohol extract from P. marsupium have revealed their ability to regenerate pancreatic beta-cells with a preserved function [121]. Among the components of P. marsupium, epicatechin and catechin, which belong to flavan-3-ols family, are composed of glycosides and esters that may be responsible for their anti-diabetic action [122].…”
Section: Pterocarpus Marsupium and Other Epicatechin-containing Plantsmentioning
confidence: 99%